Blocking Prohibited Sites Using Proxy Server In Mikrotik And Squid Proxy Debian Server At The Nurul Anwar Education Foundation Tanjungbalai City - Zulham Sitorus; Mhd Arfan Sitorus; Didi Riswan``; Heri Eko Rahmadi Putra (Yayasan Sinergi Multidimensi Kreatif, 2024)
After the internet was discovered, humans were greatly helped by internet access, both in the economic sector and in the dissemination of news or information. However, the more the internet develops, the more uses the internet has, and the internet is often misused by internet users, such as online gambling, pornography and violent content. So if there are no restrictions on accessing content or websites that contain elements that are not good and can be accessed very easily by internet users, it is feared that if minors want to open these websites, it is feared that it could damage morals. children who are still immature in using the internet, therefore a Proxy Server is needed which aims to filter internet access from prohibited sites which are likely to be accessed by users who are immature in using the internet and provide healthy internet implementation by adding a proxy server as filtering websites. filtering or blocking websites that are inappropriate for internet users. The results of this research are that the network security tool using a proxy works if there is an attempt to open a website listed on the list of websites that are not allowed to be accessed and the proxy server network security system, there is no limit to how many websites can be blocked.